Development and assessment of competency-based neurotrauma course curriculum for international neurosurgery residents and neurosurgeons (2020)
Traumatic brain injuries (TBIs) are a significant disease burden worldwide. It is imperative to improve neurosurgeons’ training during and after their medical residency with appropriate neurotrauma competencies. Unfortunately, the development of these competencies during neurosurgeons’ careers and in daily practice is very heterogeneous. This article aimed to describe the development and evaluation of a competency-based international course curriculum designed to address a broad spectrum of needs for taking care of patients with neurotrauma with basic and advanced interventions in different scenarios around the world. METHODS A committee of 5 academic neurosurgeons was involved in the task of building this course curriculum. The process started with the identification of the problems to be addressed and the subsequent performance needed. After this, competencies were defined. In the final phase, educational activities were designed to achieve the intended learning outcomes. In the end, the entire process resulted in competency and outcomes-based education strategy, including a definition of all learning activities and learning outcomes (curriculum), that can be integrated with a faculty development process, including training. Further development was completed by 4 additional academic neurosurgeons supported by a curriculum developer specialist and a project manager. After the development of the course curriculum, template programs were developed with core and optional content defined for implementation and evaluation. RESULTS The content of the course curriculum is divided into essentials and advanced concepts and interventions in neurotrauma care. A mixed sample of 1583 neurosurgeons and neurosurgery residents attending 36 continuing medical education activities in 30 different cities around the world evaluated the course. The average satisfaction was 97%. The average usefulness score was 4.2, according to the Likert scale. CONCLUSIONS An international competency-based course curriculum is an option for creating a well-accepted neurotrauma educational process designed to address a broad spectrum of needs that a neurotrauma practitioner faces during the basic and advanced care of patients in different regions of the world. This process may also be applied to other areas of the neurosurgical knowledge spectrum. Moreover, this process allows worldwide standardization of knowledge requirements and competencies, such that training may be better benchmarked between countries regardless of their income level.